Is There a Distinction in Socialization Ability Between Children Who Are addicted to Gadgets and Those Who Are Not? A Comparison Study - Wahyuni, Sri; Bastian, Adolf; Nofrianti, Septia (Jurnal Pendidikan Anak, 2021)
The social skills of kindergarten children in the Tampan district are remain low, this can be seen from the children who do not want to be left by their parents when they enter class to study, even though teachers and other friends have persuaded them to study together and those children prefer to be alone. For this reason, researchers conducted a comparative study to examine the differences in social skills between the children who are addicted and not addicted to gadgets. This research method uses a comparative descriptive quantitative approach. The population in this study are all children aged 5-6 years in kindergarten throughout the Tampan District, amounted to 194 children. The sampling technique used was the purposive technique so that the samples of this study were 30 children addicted to gadgets and 30 children who were not addicted to gadgets. Data collection techniques using observation guidelines and documentation. Based on the results of data analysis and discussion, it can be concluded that a) The social skills of children who are not addicted to gadgets with a minimum score of 59, a maximum score of 99 and an average score of 55.10, while the social skills of children who are addicted to gadgets in kindergartens throughout the Tampan district with a minimum score of 41, while a maximum score of 57 with an average of 48.27, b) Differences in the social skills of children aged 5-6 years who are addicted to gadgets in kindergartens throughout the Tampan district are shown from the test results t shows tcount (7.416) > ttable (2.00) and the significance score (0.000) < (0.05) it means Ha is accepted, while Ho is rejected. The magnitude of the difference between children who are addicted and those who are not addicted on gadgets is 6.83%.